Trophic-Mediated Pelagic Habitat Structuring and Partitioning by Sympatric Elasmobranchs - Afonso, André S.; Macena, Bruno C. L.; Mourato, Bruno; Bezerra, Natalia P. A.; Mendonça, Sibele; de Queiroz, Joyce D. G. R.; Hazin, Fábio H. V. (Frontiers in Marine Science, 2022)
Pelagic elasmobranchs are key elements of oceanic ecosystems and must be preserved if marine trophic networks are to be kept in balance. Yet, they face an intense fishing pressure which has been threatening their populations worldwide. Ensuring a proper conservation management of these taxa depends on a better understanding about the strategies they use to explore the pelagic realm and their contributions to trophic web structuring across the ocean column. This study aimed at examining relationships between vertical habitat use and trophic attributes among six sympatric pelagic elasmobranchs using satellite transmitting tags in the western equatorial South Atlantic Ocean. The vertical movements of 35 elasmobranch individuals were tracked during an overall total of 1911 days. Clear relationships between species’ feeding habit, maximum diving depths and proportion of time spent either in epipelagic as in surface waters were evidenced by Bayesian generalized linear mixed models and multivariate analysis. Filter-feeders made most use of deep waters from the mesopelagic and bathypelagic and shifted their diving depths in phase with diel vertical migrations of the deep scattering layer, i.e., shallower during the night and deeper during the day. Specialists exhibited distinct diving patterns in epipelagic and mesopelagic waters across the diel period which are potentially indicative of habitat partitioning, whereas generalists were more surface-oriented but also explored deeper waters than specialists. Trophic level also seemed to influence elasmobranch maximum diving depths, which tended to become shallower as species’ trophic level increased. These results corroborate previous evidence of widespread vertical habitat partitioning among sympatric pelagic predators and depict a trophic-mediated structuring of the pelagic environment where top-down control may be exerted at different depths by distinct species. Further research is yet required to understand the role of elasmobranch vertical movements in structuring pelagic habitats as well as to guide ecosystem-based fisheries management aimed at reducing species susceptibility to fishing gear and at preserving the structure and functionality of marine trophic networks.